Resistive Switching in Graphene Oxide - Romero, Francisco J.; Toral, Alejando; Medina-Rull, Alberto; Moraila-Martinez, Carmen Lucia; Morales, Diego P.; Ohata, Akiko; Godoy, Andres; Ruiz, Francisco G.; Rodriguez, Noel (Frontiers in Materials, 2020)
The search and investigation of resistive switching materials, the most consolidated form of solid-state memristors, has become one of the fastest growing areas in the field of electronics. This is not only due to the huge commercial interest in developing the so-called Resistive Random-Access Memories (ReRAMs) but also because resistive switching materials are gathering way to new forms of analog computation. Unlike in the field of traditional electronics technologies, where Silicon has monopolized most of the applications, the area of solid-state memristors is opened to a broad set of candidates that may contribute to unprecedented applications. In particular, the use of organic-based resistive switching materials can provide additional functionalities as structural flexibility for conformal integration or introduce new and cost-effective fabrication technologies. Following this new wave of organic memristive materials, this work aims at reviewing the existing models explaining the origins of resistive switching in Graphene Oxide, one of the most promising contenders on the battlefield of emerging memristive materials due to its low cost and easy processing methods. Within this manuscript, we will revisit the different theories supporting the phenomenology of resistive switching in this material nourishing the discussion with experimental results supporting the three main existing theories.